2010
DOI: 10.1016/s0140-6736(10)60057-8
|View full text |Cite
|
Sign up to set email alerts
|

Daily co-trimoxazole prophylaxis in severely immunosuppressed HIV-infected adults in Africa started on combination antiretroviral therapy: an observational analysis of the DART cohort

Abstract: SummaryBackgroundCo-trimoxazole prophylaxis can reduce mortality from untreated HIV infection in Africa; whether benefits occur alongside combination antiretroviral therapy (ART) is unclear. We estimated the effect of prophylaxis after ART initiation in adults.MethodsParticipants in our observational analysis were from the DART randomised trial of management strategies in HIV-infected, symptomatic, previously untreated African adults starting triple-drug ART with CD4 counts lower than 200 cells per μL. Co-trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
104
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 29 publications
9
104
1
2
Order By: Relevance
“…28 This effect was maintained throughout a follow-up period of 5 years. In addition, Walker et al also reported that cotrimoxazole reduced the odds of new or recurrent WHO clinical stage 3 or 4 disease events (OR: 0.85; 95% CI: 0.74-0.98), 28 whereas Miiro et al reported a trend towards lower all-cause morbidity (relative risk, RR: 0.66; 95% CI: 0.41-1.06), although all-cause morbidity was undefined.…”
Section: 30mentioning
confidence: 82%
See 4 more Smart Citations
“…28 This effect was maintained throughout a follow-up period of 5 years. In addition, Walker et al also reported that cotrimoxazole reduced the odds of new or recurrent WHO clinical stage 3 or 4 disease events (OR: 0.85; 95% CI: 0.74-0.98), 28 whereas Miiro et al reported a trend towards lower all-cause morbidity (relative risk, RR: 0.66; 95% CI: 0.41-1.06), although all-cause morbidity was undefined.…”
Section: 30mentioning
confidence: 82%
“…28 This effect was maintained throughout a follow-up period of 5 years. In addition, Walker et al also reported that cotrimoxazole reduced the odds of new or recurrent WHO clinical stage 3 or 4 disease events (OR: 0.85; 95% CI: 0.74-0.98), 28 whereas Miiro et al reported a trend towards lower all-cause morbidity (relative risk, RR: 0.66; 95% CI: 0.41-1.06), although all-cause morbidity was undefined. 35 A trial identified during the review of references of studies that met the inclusion criteria found that the risk of both malaria (RR: 0.04; 95% CI: 0.01-0.17) and diarrhoea (RR: 0.56; 95% CI: 0.43-0.77) was lower among Ugandans on ART who were randomized to cotrimoxazole than among those who were not.…”
Section: 30mentioning
confidence: 82%
See 3 more Smart Citations